CD4 Donor Lymphocyte Infusion Can Cause Conversion of Chimerism Without GVHD by Inducing Immune Responses Targeting Minor Histocompatibility Antigens in HLA Class II - van Balen, Peter; van Bergen, Cornelis A. M.; van Luxemburg-Heijs, Simone A. P.; de Klerk, Wendy; van Egmond, Esther H. M.; Veld, Sabrina A. J.; Halkes, Constantijn J. M.; Zwaginga, Jaap-Jan; Griffioen, Marieke; Jedema, Inge; Falkenburg, J. H. Frederik (Frontiers in Immunology, 2018)
Under non-inflammatory conditions HLA class II is predominantly expressed on hematopoietic cells. Therefore, donor CD4 T-cells after allogeneic stem cell transplantation (alloSCT) may mediate graft-versus-leukemia reactivity without graft-versus-host disease (GVHD). We analyzed immune responses in four patients converting from mixed to full donor chimerism without developing GVHD upon purified CD4 donor lymphocyte infusion (DLI) from their HLA-identical sibling donor after T-cell depleted alloSCT. In vivo activated T-cells were clonally isolated after CD4 DLI. Of the alloreactive T-cell clones, 96% were CD4 positive, illustrating the dominant role of CD4 T-cells in the immune responses. We identified 9 minor histocompatibility antigens (MiHA) as targets for alloreactivity, of which 8 were novel HLA class II restricted MiHA. In all patients, MiHA specific CD4 T-cells were found that were capable to lyse hematopoietic cells and to recognize normal and malignant cells. No GVHD was induced in these patients. Skin fibroblasts forced to express HLA class II, were recognized by only two MiHA specific CD4 T-cell clones. Of the 7 clones that failed to recognize fibroblasts, two targeted MiHA were encoded by genes not expressed in fibroblasts, presentation of one MiHA was dependent on HLA-DO, which is absent in fibroblasts, and T-cells recognizing the remaining 4 MiHA had an avidity that was apparently too low to recognize fibroblasts, despite clear recognition of hematopoietic cells. In conclusion, purified CD4 DLI from HLA-identical sibling donors can induce conversion from mixed to full donor chimerism with graft-versus-malignancy reactivity, but without GVHD, by targeting HLA class II restricted MiHA.